HUBUNGAN IKLIM ORGANISASI DAN LOYALITAS KARYAWAN PADA SEBUAH PERUSAHAAN E-COMMERCE DI JAKARTA - Yulianto, Aries; Martina, Devi (Jurnal Psikologi, 2018)
The development of e-commerce business in Indonesia has increased dramatically since the last few years. This e-commerce business development is using by an e-commerce startup companylocated in West Jakarta.Researchers found some problems related to the company and its employees. Shortly, it could be assumed that their employee loyalty and organizational climate are low. Employee loyalty is an orientation toward organization that related with personal identification to their organization. On the other hand, organizational climate is an environment qualitywithin an organization that relatively felt and stayed by an employee. The objective of this study is to determine the relationship between organizational climate and employee loyalty, by controlling the effect of age and gender on loyalty. Participants were 50 employees (21 males, 29 females) of the company, aged 23 to 34 year old (M = 27.62,SD = 2.899). This research found the correlations range from .540 and .588, p < .01. It can be concluded that there is a positive and significant correlation between organizational climate and loyalty, including whencontrolling effect of age and gender to loyalty.Â Keywords: e-commerce, loyalty, organizational climate